Feedback about action performed can alter the sense of self-agency - Kumar, Neeraj; Manjaly, Jaison A.; Miyapuram, Krishna P. (Frontiers in Psychology, 2014)
Feedback About Action Performed Can Alter the Sense of Self -Agency Neeraj Kumar, Jaison A. Manjaly and K. P. Miyapuram Cognitive Science Program, Indian Institute of Technology Gandhinagar VGEC Campus, Chandkheda, Ahmedabad-382424, INDIA Abstract Sense of agency refers to the sense of authorship of an action and its outcome. Sense of agency is often explained through computational models of motor control (e.g. the comparator model). Previous studies using the comparator model have manipulated action-outcome contingency to understand its effect on the sense of agency. More recent studies have shown that cues related to outcome, priming outcome and priming action have an effect on agency attribution. However, relatively few studies have focused on the effect of recalibrating internal predictions on the sense of agency. This study aims to investigate how feedback about action can recalibrate prediction and modulates the sense of agency. While participants performed a Flanker task, we manipulated the feedback about the validity of the action performed, independent of their responses. When true feedback is given, the sense of agency would reflect congruency between the sensory outcome and the action performed. The results show an opposite effect on the sense of agency when false feedback was given. We propose that feedback about action performed can recalibrate the prediction of sensory outcome and thus alter the sense of agency.